Pengaruh Substitusi Abu Sekam Padi terhadap Kuat Tekan dan Workability Beton Self-Compacting Concrete (SCC) sebagai Upaya Pemanfaatan Limbah Ramah Lingkungan - Hasir, Hasir; Simatupang, Minson; Mokui, Hasmina Tari; Arsyad, Febriansyah; Alson, Muh Wonua Bhakti; Pratiwi, Nanda Ayu (Sultra Civil Engineering Journal (SCiEJ), 2025)
The increasing concern for environmental sustainability has prompted innovations in the construction industry, particularly through the utilization of agricultural waste as supplementary cementitious materials. This research examines how replacing cement with rice husk ash (RHA) influences the compressive strength and workability of Self-Compacting Concrete (SCC). A comparative experimental approach was used, with Portland Composite Cement (PCC) serving as the primary binder and RHA added as a partial cement substitute at proportions of 2.5%, 5%, and 10% by weight. Prior to developing the mix design, the physical and mechanical characteristics of the aggregates were assessed following Indonesian National Standards (SNI). The compressive strength of cylindrical specimens (15 cm × 30 cm) was measured at 14 and 28 days of curing. The findings show that replacing 5% of the cement with RHA yielded the greatest compressive strength, reaching 35.7 MPa at 28 days, exceeding the strength of the control mix and other replacement levels. This enhancement is attributed to the pozzolanic activity of the amorphous silica in RHA, which improves the concrete’s microstructure and decreases its porosity. However, exceeding 5% replacement leads to reduced performance due to excessive dilution of cementitious content. Therefore, rice husk ash can be effectively utilized as an eco-friendly cement replacement up to an optimal proportion of 5%, supporting the development of sustainable construction materials in Indonesia